SPECT/CT-Guided Surgical Removal of a Positive External Iliac Sentinel Node in Primary Umbilical Melanoma: Report of a Case, and Up-to-Date Review of the Literature - Picciotto, Franco; Lesca, Adriana; Mastorino, Luca; Califaretti, Elena; Conti, Luca; Quaglino, Pietro; Ribero, Simone; Caliendo, Virginia; Deandreis, Désirée (Frontiers in Oncology, 2022)
Primary umbilical melanoma is rare tumor, representing about 5% of all umbilical malignancies. The lymphatic drainage from the tumor is challenging and can be to inguinal, axillary and retroperitoneal nodes. Dynamic and static lymphoscintigraphy with single photon emission tomography/computed tomography (SPECT/CT) and sentinel lymph node biopsy (SLNB) is a widely validated tecnique in patients with clinically localized melanoma to search for and quantify nodal spread of cutaneous melanoma. Moreover, it offers the surgeon the preoperative information about the number and location of the sentinel lymph nodes (SLNs), which makes SLNB easier and quicker. This is the first report of an ulcerated thick melanoma of the umbilicus metastasizing only to an external iliac lymph node without involvement of superficial inguinal SLNs. The preoperative high-resolution ultrasound examination of the regional lymph node field had been normal. This case-report shows how addiction of SPECT/CT to planar imaging in a patient with clinically localized umbilical melanoma can help avoid incomplete SLNB when a deep SLN is not removed. A literature review of umbilical melanoma is also provided.